Optimization of Newborn Care to Prevent Postbirth Health Disorders - Ghita, Dwi; Suhartini, Suhartini; Mustafa, Sri Resky (CV. Paperhome Indonesia, 2024)
Newborn babies (BBL) are babies aged 0 to 28 days who are able to develop with full adaptation from intrauterine to extrauterine life. Newborn babies are very vulnerable to health problems and must receive optimal care or midwife services. Apart from receiving care for newborns, the need for optimal early detection, prevention of complications and neonatal emergencies in accordance with midwifery management as a standard for health workers must also be carried out. Outreach activities regarding optimizing care for newborns in increasing the knowledge of midwives, mothers and the community regarding health problems that babies can experience after birth into the world. This is closely related to neonatal emergencies. The target of this PKM activity is to know and understand the positive impacts associated with providing optimal care for newborns